Inkjet printing of solid oral dosage forms - Cader, Hatim K. (2019)
Inkjet printing is a form of additive manufacturing where liquid droplets are selectively deposited onto a substrate, followed by solidification. This process can potentially be used to address limitations for the manufacturing of solid oral dosage forms or tablets. Conventional processes can be long and complex, making personalisation a major challenge. The main aim of this thesis was to wholly inkjet a tablet capable of delivering drug with a controlled release. To achieve this a multi-material reservoir system was designed for one-directional drug release. It consisted of three components: (i) a rapidly dissolving core, (ii) an impermeable shell (base and walls) and (iii) a release controlling membrane. The first component of the reservoir system that was developed was the rapidly dissolving core, which on its own was presented as a standalone tablet, using thiamine hydrochloride (HCl). Using a water-based ink, which was presented as a potential universal formulation for water soluble drugs, it was shown that consistent and reliable jetting behaviour was achieved. The tablet was easily removed from its substrate and could be handled without any indication of damage. Printed drug was determined to be in its desired polymorphic form and was distributed homogenously across its top and bottom surfaces, as well as across its cross-section. Rapid drug release was achieved, with 90 % of drug released within seven minutes. The impermeable shell was printed using polycaprolactone (PCL) and N, N–dimethylacetamide (DMAC) as a solvent. The prints were seen to be very sensitive to substrate temperature. A final substrate temperature of 60 °C was selected resulting in molten PCL to form on the substrate. However, when the substrate heat was turned off, a uniform solid film formed without cracking or delamination, hence it was selected. The impermeable nature of the material was demonstrated by testing systems consisting of the rapid releasing core surrounded by printed PCL. Unless the top surface of PCL broke, PCL was effective in preventing release. The release controlling membrane was developed with a blend of PCL and water-soluble polyvinylpyrrolidone (PVP). Surface characterisation techniques illustrated phase separation between the materials. PVP domains were seen to be dispersed in a PCL matrix. When exposed to water, the PVP dissolved providing a pathway for drug release. With the application of this release controlling membrane (25 printed layers) controlled release was achieved and zero-order kinetics were exhibited. By varying not just the PVP loadings in the ink, but also different printing parameters, the thickness of the membrane and its pore area sizes were controlled, influencing releasing. Several different drug release profiles were achieved in this thesis including rapid, controlled extended, delayed and a bimodal (fast to slow) drug release.